Vascular health late after Kawasaki disease: implications for accelerated atherosclerosis - Yiu-Fai Cheung (Korean Pediatric Society, 2014)
Kawasaki disease (KD), an acute vasculitis that primarily affects young children, is the most common acquired paediatric cardiovascular disease in developed countries. While sequelae of arterial inflammation in the acute phase of KD are well documented, its late effects on vascular health are increasingly unveiled. Late vascular dysfunction is characterized by structural alterations and functional impairment in term of arterial stiffening and endothelial dysfunction and shown to involve both coronary and systemic arteries. Further evidence suggests that continuous low grade inflammation and ongoing active remodeling of coronary arterial lesions occur late after acute illness and may play a role in structural and functional alterations of the arteries. Potential importance of genetic modulation on vascular health late after KD is implicated by associations between mannose binding lectin and inflammatory gene polymorphisms with severity of peripheral arterial stiffening and carotid intima-media thickening. The changes in cholesterol and lipoproteins levels late after KD further appear similar to those proposed to be atherogenic. While data on adverse vascular health are less controversial in patients with persistent or regressed coronary arterial aneurysms, data appear conflicting in individuals with no coronary arterial involvements or only transient coronary ectasia. Notwithstanding, concerns have been raised with regard to predisposition of KD in childhood to accelerated atherosclerosis in adulthood. Until further evidence-based data are available, however, it remains important to assess and monitor cardiovascular risk factors and to promote cardiovascular health in children with a history of KD in the long term.